Merancang Struktur Konsep Pengembangan Bahan Ajar PAI Dengan Mengadaptasi Beragam Sumber Informasi Hasil Riset Termutakhir - Akbar, Ahmad; Wahyudi, Annisa Rezki Eka Putri; Agustiawan, Mochammad Pandu; Nugraha, Muhammad Tisna; Kurniawan, Citra (Jurnal Ilmiah Global Education, 2024)
The development of teaching materials in Islamic Education (PAI) is crucial to facilitate effective learning experiences. This paper outlines a structured conceptual framework for designing PAI teaching materials by integrating various up-to-date research findings. The framework is informed by contemporary educational theories and pedagogical practices, aiming to enhance the quality and relevance of PAI instruction in diverse educational settings. By synthesizing recent research on learning styles, cognitive processes, and instructional strategies, the proposed framework emphasizes the importance of incorporating interactive and engaging elements into PAI materials. Furthermore, it advocates for the integration of digital technologies to cater to the preferences and needs of modern learners. The conceptual framework presented in this paper serves as a guide for educators and curriculum developers in creating comprehensive and effective PAI teaching materials that promote meaningful learning outcomes and foster a deeper understanding of Islamic principles and values.